Internal Factors Affecting The Micro Credit Non Performing Loan (Case Study: BPR Wahana Sentra Artha) - Faisal Faisal; Dedi Walujadi; Anwar Rahim (Jurnal Manajemen, 2018)
The purpose of this study was to analyze the internal factors rural banks (BPR) and strategies to provide micro-credit to the non-performing loan (NPL). The research was conducted in the BPR Wahana Sentra Artha District Majalengka, Sumedang Regency, Regency Sukabumi and Cirebon Regency of West Java Province. The sampling technique used in this research is purposive sampling technique of data analysis of this study was to test multiple regression and linear regression. Hypothesis testing results show that the internal conditions BPR positive and significant impact on the strategy of credit, debtor conditions positive and significant impact on the strategy of lending, and credit strategies and significant negative effect on the NPL.